2018
DOI: 10.4067/s0718-221x2018005002801
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of the surface of heat-treated juvenile teak wood assessed by drop shape analyzer

Abstract: This study investigated the effect of the heat treatment on the wettability of the surface of juvenile teak (Tectona grandis) wood assessed by drop shape analyzer. Heartwood and sapwood samples were heat-treated at 180 and 200ºC. Contact angle measurements were done every 5 s for 120 s using a KRÜSS DSA100. Heartwood had lower wettability than sapwood. Heat-treatment decreased the surface wettability of both heartwood and sapwood, especially in the wood treated at 200ºC. Heartwood had lower wettability than sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…This implies that the wood surface wettability was clearly degraded after the heat treatment process due to the surface inactivity. Some researchers [14,[22][23][24][25] observed a similar behaviour i.e. decreased wettability which means contact angle increased for wood sample treated at different higher temperature.…”
Section: Surface Wettability (Contact Angle)mentioning
confidence: 81%
See 1 more Smart Citation
“…This implies that the wood surface wettability was clearly degraded after the heat treatment process due to the surface inactivity. Some researchers [14,[22][23][24][25] observed a similar behaviour i.e. decreased wettability which means contact angle increased for wood sample treated at different higher temperature.…”
Section: Surface Wettability (Contact Angle)mentioning
confidence: 81%
“…Ayrilmis et al [18] investigated the effect of heat treatment on adhesive bonding performance and concluded that the bonding strength of the heat-treated medium density fiberboard panels decreased with increasing contact angle even though the surface roughness improved. Surface wettability mechanism of material after heat treatment plays an important role for the bond performance [22][23][24][25].…”
mentioning
confidence: 99%
“…After heat treatment, the lignin content increased, while carboxylic acid functions that are mainly present in hemicelluloses decreased significantly; an important decrease in wood acidity was noted [35]. The dehydration reactions of hemicelluloses that are ongoing during heat-treatment are able to degrade OH-groups, which cause a decrease in water penetration into the wood surface [36]. The heat treatment causes a greater gas permeability and an increase in porosity and decrease in gravimetric density [37][38][39].…”
Section: Resultsmentioning
confidence: 99%
“…This complex phenomenon is related to various factors, e.g. , cell morphology, roughness, specific surface area, permeability, functional groups, and molecular and elemental compositions . Its porous structures on the surface and high contents of hydroxyl groups adversely lead to increased water absorption, which can cause swelling, dimensional instability, cracking, and degradation of the wood.…”
Section: Introductionmentioning
confidence: 99%
“…This complex phenomenon is related to various factors, e.g., cell morphology, roughness, specific surface area, permeability, functional groups, and molecular and elemental compositions. 3 Its porous structures on the surface and high contents of hydroxyl groups adversely lead to increased water absorption, which can cause swelling, dimensional instability, cracking, and degradation of the wood. To solve this problem, many studies have focused on chemical modifications of the wood structures by converting their hydrophilic surfaces using hydrophobic compounds, endowing the wood materials with water resistance and prolonged service life.…”
Section: Introductionmentioning
confidence: 99%